A two-dimensional layered proton exchange membrane with stable and high proton conductivity, and a preparation method and application thereof

By constructing hierarchical two-dimensional nanochannels with hydrophilic-hydrophobic-hydrophilic layers between two-dimensional nanosheets, the problems of low proton conductivity and easy swelling of two-dimensional layered proton exchange membranes are solved, achieving a balance between efficient proton transport and structural stability, which is suitable for applications such as fuel cells and flow batteries.

CN123034008APending Publication Date: 2026-11-03WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611128046.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing two-dimensional layered proton exchange membranes suffer from low proton conductivity and easy swelling. They lack synergistic regulation of the interlayer and interfacial water environment, making it difficult to achieve both efficient proton transport and structural stability.

Method used

By pretreating two-dimensional nanosheets with H+ exchange and using cationic amphiphilic organic molecules for interface-oriented assembly in a two-dimensional confined space, a hierarchical two-dimensional nanochannel with hydrophilic-hydrophobic-hydrophilic properties is constructed, forming a continuous proton transport region and a structural confinement region.

Benefits of technology

It achieves stable and efficient proton conduction, improves the structural stability and anti-swelling performance of the membrane, and is suitable for fuel cells, flow batteries and acid recovery membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a two-dimensional layered proton exchange membrane with stable and high proton conductivity as well as a preparation method and application thereof. The proton exchange membrane is assembled and constructed by ion-exchanged two-dimensional nanosheets and positively charged amphiphilic modifiers. The hydrophilic groups of the amphiphilic modifiers can form a hydrophilic region and a continuous hydrogen bond network on the surface of the two-dimensional nanosheets, reduce the proton transmission energy barrier and promote the rapid conduction of protons. The hydrophobic carbon chains can be oriented and distributed in the interlayer space to form a hydrophobic region, which is used for inhibiting the swelling of the sheet layer to maintain the stability of the thin film, thereby constructing a hydrophilic-hydrophobic-hydrophilic hierarchical structure in the two-dimensional transmission channel, realizing the stable and efficient transmission of protons. The application combines the H + ion exchange, amphiphilic modifier functionalization assembly and film forming treatment and other processes. The obtained proton exchange membrane has the advantages of high proton conductivity, excellent stability and good flexibility and is suitable for fuel cell proton exchange membranes, flow battery separators and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of proton exchange membrane technology for fuel cells, specifically relating to a layered proton exchange membrane based on the interface structure regulation within a two-dimensional nano-confined space, its preparation method, and its application. Background Technology

[0002] With the rapid development of new energy, fuel cells, and electrochemical energy storage, high-performance proton exchange membrane (PEM) materials have attracted widespread attention. As a core functional material in fuel cells, the PEM's main function is to achieve efficient proton conduction while blocking electrons and reactant gases, thereby ensuring efficient and stable energy conversion. Currently, PEMs are mainly based on perfluorosulfonic acid polymer membranes and their composite membranes, which are widely used in fuel cells and other fields.

[0003] In recent years, two-dimensional layered membranes constructed from stacked two-dimensional nanosheets have shown promising application prospects in the field of proton conduction due to their advantages such as continuous and ordered two-dimensional nanochannels, tunable interlayer structures, and excellent thermal stability. By controlling the two-dimensional nanochannels and interface structures, the proton transport performance and structural stability of membrane materials can be further optimized. Therefore, two-dimensional layered proton exchange membranes have gradually become an important research direction in the field of new energy membrane materials.

[0004] Unlike the disordered arrangement of proton channels in polymer membranes, two-dimensional layered membranes composed of stacked nanosheets possess continuous and ordered two-dimensional nanochannels and natural thermal stability, which is beneficial for rapid proton transport and can overcome the conduction limitations of traditional polymer films. However, existing two-dimensional layered membranes still have the following problems: (1) The intrinsic proton carriers of two-dimensional materials are limited, making it difficult to provide continuous and high-density proton migration paths, which to some extent limits the further improvement of their proton conduction performance; (2) Two-dimensional nanochannels are prone to water absorption and swelling, gradually destroying the integrity of the channels and membranes, leading to performance degradation. In addition, existing research on the regulation of two-dimensional layered proton exchange membranes mainly focuses on the single regulation of increasing hydrophilic proton carriers, lacking synergistic regulation of the interlayer and interfacial water environment of the membrane, making it difficult to ensure efficient proton transport while inhibiting membrane swelling to maintain structural stability. Therefore, how to achieve efficient proton transport and structural stability maintenance in two-dimensional nanochannels is an important problem that needs to be solved in the current development of two-dimensional layered proton exchange membranes. Summary of the Invention

[0005] The main objective of this invention is to address the problems and shortcomings of current proton exchange membranes by providing a two-dimensional layered proton exchange membrane, achieved through H2O fabrication of two-dimensional nanosheets. +Exchange pretreatment and the use of cationic amphiphilic organic molecules with interfacial directional assembly capabilities to regulate the interlayer structure of two-dimensional nanosheets enable the amphiphilic molecules to form an ordered arrangement within the two-dimensional confined space, thereby constructing hierarchical two-dimensional nanochannels with continuous proton transport regions and structural constraint regions; the construction of ordered hydrophilic-hydrophobic-hydrophilic hierarchical two-dimensional nanochannels between layers can achieve stable and efficient proton conduction.

[0006] Another objective of this invention is to provide a method for preparing a two-dimensional layered proton exchange membrane with stable and high proton conductivity. This method is simple and highly scalable.

[0007] Another objective of this invention is to provide an application of a two-dimensional layered proton exchange membrane with stable and high proton conductivity in the fields of fuel cell proton exchange membranes, flow battery membranes, and acid recovery membranes.

[0008] To achieve the above-mentioned objectives, the specific technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a two-dimensional layered proton exchange membrane with stable and high proton conductivity. The proton exchange membrane is made of H... + The exchanged two-dimensional nanosheets are synergistically assembled with cationic amphiphilic organic regulatory molecules to form a hierarchical two-dimensional nanochannel with hydrophilic-hydrophobic-hydrophilic layers.

[0009] Preferably, the two-dimensional nanosheets are selected from one or more of montmorillonite, vermiculite, saponite, mica, kaolinite, illite, graphene, graphynylene, metal disulfide, MXene, COF, MOF, etc.

[0010] Preferably, the two-dimensional nanosheet has a lateral dimension of 100 nm-20 μm and a thickness of 0.3-5 nm.

[0011] Preferably, the amphiphilic modifier is positively charged and contains hydrophilic and hydrophobic groups.

[0012] Preferably, the hydrophilic group includes one or more of amino, guanidinyl, amidoyl, imidazole, and quaternary ammonium groups.

[0013] Preferably, the hydrophobic group includes one or more of alkyl chains, aromatic rings, and fluorocarbon chains.

[0014] Preferably, the hydrophilic groups in the amphiphilic modifier are adsorbed onto the surface of the two-dimensional nanosheets through electrostatic interactions and hydrogen bonding, forming continuous hydrophilic regions and hydrogen bond networks at the layer interfaces; while the hydrophobic groups are oriented in the interlayer space to form hydrophobic water areas, which are used to regulate the interlayer water environment and inhibit film swelling.

[0015] Furthermore, the amphiphilic modifier may be selected from one or more of the following: primary alkylamines, quaternary ammonium salts, aromatic amidines, fluorocarbon amine salts, etc.

[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned two-dimensional layered proton exchange membrane with stable and high proton conductivity, specifically comprising the following steps: (1) Add the two-dimensional nanosheet suspension to a solution containing H + Ion exchange is performed in an acidic solution to completely exchange the interlayer cations of the two-dimensional nanosheets for H+, which is required for the proton exchange membrane. + H + Exchange-modified two-dimensional nanosheet suspension; (2) H + A two-dimensional nanosheet suspension modified by exchange and a positively charged amphiphilic modifier were added to water and uniformly dispersed to obtain a functionalized two-dimensional nanosheet suspension, wherein a hydrophilic-hydrophobic water interface was formed in the two-dimensional nanosheet channel. (3) The suspension obtained in step (2) is cast onto the surface of the base membrane and dried to obtain a two-dimensional layered proton exchange membrane.

[0017] Preferably, in step (1), the solution contains H+. + Inorganic or organic acid solutions.

[0018] Preferably, in step (1), the concentration of the acid solution is 0.1 mmol / L. -1 -5mol L -1 .

[0019] Preferably, in step (1), the ion exchange is carried out at room temperature to 80°C for 0.5-48 hours.

[0020] Preferably, in step (2), the concentration of the two-dimensional nanosheets in the two-dimensional nanosheet suspension is 0.05-2 wt%.

[0021] Preferably, in step (2), the amount of the amphiphilic modifier is 0.5-50% of the mass of the two-dimensional nanosheets.

[0022] Preferably, in step (2), the amphiphilic agent is directly added or prepared into a solution for modification, and the concentration of the solution is 0.1-30wt%.

[0023] Preferably, in step (3), the base membrane is selected from one of polyvinylidene fluoride membrane, polyethersulfone membrane, polysulfone membrane, polyacrylonitrile membrane, polyamide membrane, polytetrafluoroethylene membrane, nylon membrane or other organic polymer porous membranes with supporting function, and the pore size of the base membrane is generally in the range of 0.1-5 micrometers.

[0024] Preferably, the casting method in step (3) includes one or more of the following: filtration, coating, spraying, spin coating, casting, or interface assembly.

[0025] In a third aspect, the present invention provides a two-dimensional layered proton exchange membrane that can be applied to proton exchange membranes for fuel cells, flow battery membranes, and acid recovery membranes, and has high proton conductivity, good stability, and anti-swelling properties.

[0026] The principle of this invention is as follows: This invention is based on the structural characteristics of the sub-nanometer confined space between two-dimensional nanosheets, and utilizes H... + Interfacial pretreatment and the directional assembly of cationic amphiphilic organic regulatory molecules enable synergistic regulation of the interfacial microenvironment of two-dimensional nanosheets, thereby constructing two-dimensional confined nanochannels with stable proton transport capabilities. This solves the problems of low conductivity and easy swelling of two-dimensional proton exchange membranes. Further, amphiphilic modifiers are introduced to regulate the structure of the two-dimensional nanosheets, promoting the formation of hierarchical two-dimensional nanomass transfer channels with hydrophilic-hydrophobic-water-hydrophilic structures. The two-dimensional nanosheets are selected from layered silicate materials, carbon-based materials, or other two-dimensional materials, possessing nanometer-scale thickness and micrometer or submicrometer-scale lateral dimensions, enabling them to form layered stacked structures during film formation. The amphiphilic modifier comprises positively charged hydrophilic groups and hydrophobic carbon chains. The hydrophilic groups interact with the negatively charged hydrophilic nanosheets primarily through electrostatic, hydrogen bonding, and hydrophilic interactions, forming continuous, ordered, strongly hydrogen-bonded proton transport channels at the film interface. This reduces the tortuosity of the transport path, lowers the proton transport energy barrier, and significantly improves proton transport efficiency. The hydrophobic groups are selected from one or more of alkyl chains, aromatic rings, or fluorocarbon chains, and are oriented within the two-dimensional nanochannel layers, inhibiting channel swelling and maintaining channel stability. In the preparation process, two-dimensional nanosheets and the amphiphilic modifier are mixed in water to form a uniformly dispersed two-dimensional nanosheet suspension. Subsequently, two-dimensional nanosheet layers are constructed on a base film using methods such as filtration, coating, spraying, spin coating, casting, or interface assembly. After drying, a two-dimensional layered proton exchange membrane with continuous transport channels is obtained. Through the synergistic effect of the above structural design and preparation methods, a hierarchical hydrophilic-hydrophobic-water-based two-dimensional nanomass transfer channel is constructed between the two-dimensional nanosheet layers, thereby achieving stable and efficient proton conduction.

[0027] Compared with the prior art, the beneficial effects of the present invention include: (1) This invention is the first to propose inducing the directional arrangement of amphiphilic molecules in a two-dimensional sub-nanometer confined space to realize the reconstruction of the interfacial water environment, rather than simply designing hydrophilic / hydrophobic structures.

[0028] (2) This invention utilizes H + The synergistic effect of exchange and amphiphilic interface regulation effectively improves interlayer proton transport capability, enabling H... +Two-dimensional nanosheets are self-assembled with positively charged amphiphilic modifiers. By utilizing the electrostatic, hydrogen bonding, and hydrophilic interactions between the positively charged hydrophilic groups in the modifiers and the negatively charged hydrophilic nanosheets, continuous and ordered strong hydrogen bond proton transport channels are effectively constructed at the film interface, reducing the tortuosity of the transport path, lowering the proton transport energy barrier, and significantly improving the proton transport efficiency.

[0029] (3) The present invention achieves synergistic regulation of the intramembrane channel structure and the interlayer water environment through the structural characteristics of the amphiphilic modifier. The hydrophilic groups interact with the surface of the two-dimensional nanosheets to construct a stable hydrophilic proton transport domain, which promotes the efficient migration of protons in the channel. At the same time, the hydrophobic carbon chains are exposed in the interlayer space and are oriented to form interlayer hydrophobic water to inhibit film swelling and maintain channel stability, thereby effectively ensuring film stability while achieving efficient proton conduction.

[0030] (4) By controlling the length of the hydrophobic carbon chain in the amphiphilic modifier molecule, the present invention can achieve precise control of the interlayer channel size and the spatial distribution of hydrophilic-hydrophobic-hydrophilic water, thereby achieving customized proton conduction performance and structural stability of the thin film. Attached Figure Description

[0031] Figure 1 This is a scanning electron microscope image of the cross-section of the thin film obtained in Example 1.

[0032] Figure 2 This is an EDS scan image of the thin film cross-section obtained in Example 1.

[0033] Figure 3 The proton conductivity is the result of an 8000-minute long-term test of the thin film obtained in Example 1.

[0034] Figure 4 The water molecules in the thin film (TMMT) obtained in Example 1 and the montmorillonite thin film (MMT) without TDA modification have strong, weak, and non-hydrogen bonded OH stretching vibrations and various hydrogen bonds in corresponding proportions.

[0035] Figure 5 The 1H NMR spectra of the TMMT and MMT films obtained in Example 1 are shown.

[0036] Figure 6 The results are molecular simulations of the H2O density distribution within the nanochannels of the TMMT thin film obtained in Example 1.

[0037] Figure 7 This is a schematic diagram of the hierarchical two-dimensional nanochannels between the layers of the proton exchange membranes obtained in Examples 1-3, which are hydrophilic-hydrophobic-hydrophilic.

[0038] Figure 8 Photograph of the TMMT thin film prepared in Example 1.

[0039] Figure 9 a) Comparison of proton conductivity between HMMT film and TMMT film prepared in Comparative Example 1; b) Comparison of swelling ratio between HMMT film and TMMT film prepared in Comparative Example 1. Detailed Implementation

[0040] To more clearly illustrate the technical objectives, implementation schemes, and advantages of the present invention, a detailed description is provided below with reference to several specific embodiments. It should be understood that these embodiments are merely illustrative descriptions intended to aid in understanding the present invention and are not intended to limit the scope of protection of the present invention.

[0041] Example 1 A two-dimensional layered proton exchange membrane with stable and high proton conductivity is prepared by the following steps: (1) Weigh out montmorillonite nanosheets with a transverse size of about 0.1 μm and an average sheet thickness of 1.4 nm.

[0042] First, two-dimensional montmorillonite nanosheets were added to 1 mmol L -1 Ion exchange was performed in HCl solution (magnetic stirring at room temperature for 12 h) to replace the interlayer cations of montmorillonite nanosheets with H+. + Then, it was repeatedly washed with deionized water to remove excess HCl until the nanosheet suspension was neutral, yielding H. + Two-dimensional montmorillonite nanosheets.

[0043] (2) Take tetradecylamine (TDA) and dissolve it in deionized water to prepare a TDA solution with a mass fraction of 0.1 wt%. Slowly add the TDA solution to the above-mentioned H at a ratio of 5% of the mass of montmorillonite nanosheets. + In a suspension of montmorillonite nanosheets, the concentration of montmorillonite nanosheets was 0.1 wt%, and the suspension was dispersed by stirring at room temperature for 24 h to obtain a functionalized modified montmorillonite nanosheet suspension.

[0044] (3) Modified montmorillonite nanosheets were filtered onto a polyethersulfone substrate (pore size ≈ 0.22 μm) by vacuum filtration to form a membrane. The membrane was then naturally dried at room temperature and peeled off to obtain a self-supporting TDA-modified two-dimensional montmorillonite proton exchange membrane (TMMT).

[0045] The cross-sectional scanning electron microscope image of the thin film product obtained in this embodiment is shown below. Figure 1 As shown, the prepared film exhibits a two-dimensional nanochannel structure composed of orderly stacked layers of montmorillonite nanosheets, providing a channel basis for ion conduction.

[0046] Figure 2 The image shows a cross-sectional EDS scan of the thin film product obtained in this embodiment. It can be seen that the introduced TDA molecules are uniformly distributed within the film.

[0047] The proton conductivity of the obtained TMMT film was further tested using a nanofluidic testing device. First, a long-term experiment of 8000 min was conducted at room temperature, and the results are as follows: Figure 3 As shown, the results indicate that the obtained thin film exhibits stable high proton conductivity during long-term testing, reaching 170 mS / cm at room temperature. -1 .

[0048] During the above modification and assembly process, Figure 4 Fourier transform infrared spectroscopy results show that the proportion of strong hydrogen bonds in the nanochannels is significantly increased after modification by the method described in this invention, indicating that a more dense and ordered hydrogen bond network is formed between the functional agent (cationic amphiphilic organic regulatory molecule) and the nanosheet interface. Figure 5 The nuclear magnetic resonance results further indicate that the hydrophilic groups in the functional agent can interact with the interlayer water molecules and the nanosheet surface, resulting in a more uniform confined distribution of water molecules in the interlayer, thereby constructing a continuous hydrogen bond transport network and promoting rapid proton conduction.

[0049] Further molecular simulation calculations were performed on the two-dimensional layered proton exchange membrane obtained in this embodiment, and the results showed that ( Figure 6 The hydrophilic groups of TDA molecules form hydrophilic regions on the surface of the nanosheets; at the same time, the alkyl chains are oriented in the interlayer space to form relatively hydrophobic regions, thereby constructing a hydrophilic-hydrophobic-hydrophilic hierarchical structure between the two-dimensional montmorillonite layers. Figure 7 This is beneficial for forming continuous proton transport channels and improving the structural stability of the membrane.

[0050] Furthermore, the film prepared in this embodiment is highly flexible and did not break when bent 180°. Figure 8 ).

[0051] Application Example 1 The two-dimensional layered proton exchange membrane obtained in this embodiment is used for acid recovery. The specific steps include the following: The two-dimensional layered proton exchange membrane prepared in Example 1 is placed in a two-chamber diffusion device, and a high-concentration hydrochloric acid solution (1 mol L) is added to one side. -1 On the other side, deionized water is added, and the H+ is driven by the concentration difference across the membrane. + Migration; then detect H in the solution on the other side. + Concentration changes.

[0052] The results show that the two-dimensional layered proton exchange membrane prepared in this embodiment can achieve H+ exchange under the drive of hydrochloric acid concentration gradient. + The continuous directional migration of H in the receiving chamber +The concentration gradually increased with diffusion time, indicating that the membrane has good proton transport capacity and high proton selective permeability. During continuous operation, the membrane did not exhibit obvious interlayer delamination, rupture, or severe swelling.

[0053] The above results indicate that the two-dimensional layered proton exchange membrane prepared by this invention can achieve efficient and stable selective proton migration in acidic systems, and also has excellent structural stability and anti-swelling properties. It can be applied to acid recovery and acid separation in acidic systems such as hydrochloric acid, sulfuric acid, and nitric acid.

[0054] Example 2 A two-dimensional layered proton exchange membrane with stable and high proton conductivity is prepared by the following steps: (1) Weigh out single-layer graphene nanosheets, wherein the graphene nanosheets have a lateral dimension of 5 μm and a thickness of 0.5 nm. First, add the graphene nanosheets to 1 mol L -1 Graphene nanosheets were fully dispersed in hydrochloric acid (HCl) solution by magnetic stirring at room temperature for 12 h. They were then washed by centrifugation and repeatedly rinsed with deionized water until neutral to obtain H... + Type of graphene nanosheets.

[0055] (2) Take another benzamide and dissolve it in deionized water to prepare a benzamide solution with a mass fraction of 1 wt%. Add the benzamide solution slowly to the above-mentioned H2O solution at a ratio of 20% of the mass of the graphene nanosheets. + In a graphene dispersion, the mixture was stirred continuously at room temperature for 2 h to allow benzidine molecules to fully contact and interact with the surface of graphene nanosheets, resulting in a functionalized graphene nanosheet suspension.

[0056] (3) The above suspension was coated onto the surface of a porous polytetrafluoroethylene (PTFE) substrate membrane using a blade coating method. The PTFE porous substrate membrane has a pore size of 0.22 μm. During the blade coating process, the blade gap was controlled at 700 μm to ensure that the modified graphene nanosheet suspension was evenly spread on the substrate membrane surface to form a wet film layer. After the blade coating was completed, the resulting wet film was dried at 50 °C for 2 h to remove residual moisture and promote the densification of the membrane structure, ultimately obtaining a benzamide-modified two-dimensional layered graphene proton exchange membrane.

[0057] During the above modification and assembly process, the hydrophilic amidine group in the benzamide molecule forms a hydrophilic region on the surface of the nanosheet; at the same time, its aromatic ring structure is oriented in the interlayer space to form a relatively hydrophobic region, thereby constructing a hydrophilic-hydrophobic-hydrophilic hierarchical structure in the interlayer of two-dimensional graphene, forming a continuous proton transport channel and improving the structural stability of the membrane.

[0058] Example 3 A two-dimensional layered proton exchange membrane with stable and high proton conductivity is prepared by the following steps: (1) Weigh out metal disulfide nanosheets, wherein the metal disulfide nanosheets are molybdenum disulfide (MoS2) nanosheets with a lateral dimension of approximately 2 μm and a thickness of approximately 3 nm. First, add the MoS2 nanosheets to 0.5 mol L -1 In an oxalic acid (H₂C₂O₄) solution, the mixture was magnetically stirred for 12 h at room temperature to allow H₂ to form. + Ion exchange occurs within the MoS2 interlayer, followed by washing by centrifugation and repeated rinsing with deionized water until neutral, yielding H2O. + Type MoS2 nanosheets.

[0059] (2) The ion-exchanged MoS2 nanosheets were added to a mixed solvent of deionized water and ethanol, wherein the volume ratio of deionized water to ethanol was 1:1, to prepare a MoS2 nanosheet dispersion with a mass fraction of 0.8 wt%. The dispersion was magnetically stirred at room temperature for 24 h and then ultrasonically treated for 60 min to obtain a uniform and stable H2O. + MoS2 nanosheet suspension.

[0060] (3) Dissolve perfluorooctyl ethylamine salt in deionized water to prepare a 1 wt% perfluorooctyl ethylamine salt solution. Slowly add the perfluorooctyl ethylamine salt solution to the above-mentioned H2O solution at a ratio of 40% of the mass of the perfluoroalkyl primary amine salt to the MoS2 nanosheets. + In a MoS2 nanosheet dispersion, the mixture was continuously stirred at room temperature for 12 h to allow the perfluorooctyl ethylamine salt molecules to fully contact the surface of the MoS2 nanosheets and undergo interfacial interactions, resulting in a functionalized MoS2 nanosheet suspension.

[0061] (4) The modified MoS2 nanosheet suspension was sprayed onto the surface of a polyacrylonitrile (PAN) porous base membrane with an average pore size of 1 μm. During the spraying process, the spraying pressure was controlled at 0.3 MPa, the distance between the spray gun and the base membrane was 10 cm, and multiple reciprocating spraying methods were used to ensure that the modified MoS2 nanosheet suspension was uniformly deposited on the base membrane surface to form a wet film layer. After the spraying was completed, the obtained wet film was dried at 50 °C for 6 h to remove residual solvent and promote the densification of the membrane structure, finally obtaining a two-dimensional layered MoS2 proton exchange membrane modified with perfluorooctyl ethylamine salt.

[0062] During the above modification and assembly process, the hydrophilic groups of the amine salt in the perfluorooctyl ethylamine salt molecule form hydrophilic regions on the surface of the nanosheet; at the same time, its perfluoroalkyl chains are oriented and distributed in the interlayer space to form relatively hydrophobic regions, thereby constructing a hydrophilic-hydrophobic-hydrophilic hierarchical structure in the two-dimensional MoS2 interlayer, forming a continuous proton transport channel, and improving the structural stability of the membrane through the confinement effect of the hydrophobic chains on the interlayer space.

[0063] Comparative Example 1 A two-dimensional layered membrane is prepared in a manner largely the same as in Example 1, except that natural montmorillonite is subjected to H+ treatment with hydrochloric acid. + After exchange treatment, the nanosheets were washed with deionized water until neutral to obtain H-MMT nanosheets. Subsequently, the H-MMT nanosheets were redispersed in deionized water and ultrasonically dispersed to form a uniform suspension. Without adding any amphiphilic organic regulating molecules, the suspension was directly filtered to form a membrane, which was then dried to obtain the HMMT membrane.

[0064] Test results show that: Although H + Exchange increased the number of interlayer proton transport sites, but due to the lack of interfacial structure regulation, the arrangement of water molecules between nanosheets remained relatively disordered, making them prone to water absorption and swelling. This resulted in poor continuity of the proton transport channels, thus the proton conductivity of the film prepared in the comparative example was significantly lower than that in Example 1. Figure 9 a), while the membrane's anti-swelling performance decreased significantly ( Figure 9 b).

[0065] Comparative Example 2 A two-dimensional layered membrane, prepared in a manner largely the same as in Example 1, differing only in that: natural montmorillonite is not subjected to H2O. + The exchange process directly prepares a nanosheet suspension.

[0066] Test results show that the proton conductivity of the obtained membrane is only 98 mS cm⁻¹. -1 The value is far lower than that of Example 1.

[0067] The embodiments described above are merely illustrative of the core concept of the present invention and do not constitute a limitation on the technical solutions of the present invention. Those skilled in the art can make various changes or optimizations to its form, structure, parameters, or process steps without departing from the basic design concept of the present invention, and such changes, optimizations, or equivalent substitutions should all fall within the scope of protection claimed by the present invention. The scope of protection of the present invention is defined by the claims.

Claims

1. A two-dimensional layered proton exchange membrane with stable and high proton conductivity, characterized in that, It is derived from H + Two-dimensional nanosheets pretreated by exchange are assembled with positively charged amphiphilic modifiers to form a two-dimensional mass transfer channel with a hierarchical hydrophilic-hydrophobic-hydrophilic structure.

2. The two-dimensional layered proton exchange membrane according to claim 1, characterized in that, The average diameter of the two-dimensional nanosheets is 100 nm-10 μm, and the average thickness of the sheets is 0.3-5 nm. The two-dimensional nanosheets are one or more of montmorillonite, vermiculite, saponite, mica, kaolinite, illite, graphene, graphyne, molybdenum disulfide, MXene, COF, and MOF.

3. The two-dimensional layered proton exchange membrane according to claim 1, characterized in that, The amphiphilic modifier has a positively charged hydrophilic group and a hydrophobic carbon chain; the hydrophilic group is one or more of amino, protonated amine, quaternary phosphorus, guanidine, and amidine; the hydrophobic carbon chain is selected from one or more of alkyl chain, aromatic ring, and fluorocarbon chain.

4. A method for preparing the two-dimensional layered proton exchange membrane according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Add the two-dimensional nanosheet suspension to a solution containing H + Ion exchange is performed in the solution to obtain H+. + Exchange-modified two-dimensional nanosheet suspension; (2) H + A suspension of exchange-modified two-dimensional nanosheets was added to water and uniformly dispersed with a positively charged amphiphilic modifier to obtain a functionalized two-dimensional nanosheet suspension. (3) Cast the suspension obtained in step (2) onto the surface of the base membrane, dry it, and obtain a two-dimensional layered proton exchange membrane.

5. The method for preparing a two-dimensional layered proton exchange membrane according to claim 4, characterized in that, In step (1), the solution contains H+. + An inorganic or organic acid solution; the acid solution concentration is 0.1 mmol / L. -1 -5 mol L -1 The ion exchange was carried out at room temperature to 80°C for 0.5-48 h.

6. The method for preparing a two-dimensional layered proton exchange membrane according to claim 4, characterized in that, In step (2), the concentration of two-dimensional nanosheets in the suspension is 0.05-2 wt%; the amount of amphiphilic modifier is 0.5-50% of the mass of the two-dimensional nanosheets.

7. The method for preparing a two-dimensional layered proton exchange membrane according to claim 4, characterized in that, In step (2), the amphiphilic modifier is added directly or prepared into a solution for modification, with a solution concentration of 0.1-30 wt%.

8. The method for preparing a two-dimensional layered proton exchange membrane according to claim 4, characterized in that, In step (3), the base membrane is one of polyvinylidene fluoride membrane, polyethersulfone membrane, polysulfone membrane, polyacrylonitrile membrane, polyamide membrane, polytetrafluoroethylene membrane, and nylon membrane; the casting method in step (3) includes one or more of vacuum filtration, coating, spraying, spin coating, casting, and interface assembly.

9. The method for preparing a two-dimensional layered proton exchange membrane according to claim 4, characterized in that, In step (3), the film drying method can be air drying or oven drying, with a drying temperature of 20-120 ℃ and a drying time of 0.5-24 h.

10. The application of the two-dimensional layered proton exchange membrane according to any one of claims 1 to 3 in fuel cell proton exchange membranes, flow battery membranes, or acid recovery membranes.